Microbial resistance and resilience to drought under organic and conventional farming - Kost, Elena; Kundel, Dominika; Conz, Rafaela Feola; Mäder, Paul; Krause, Hans-Martin; Six, Johan; Mayer, Jochen; Hartmann, Martin (bioRxiv, 2024)
The impacts of climate change, such as drought, can affect soil microbial communities. These communities are crucial for soil functioning and crop production. Organic and conventional cropping systems promote distinct soil microbiomes and soil organic carbon contents, which might maintain different capacities to mitigate drought effects on cropping systems. A field-scale drought simulation was performed in long-term organically and conventionally managed cropping systems differing in fertilization and pesticide application. The soil microbiome was assessed during and after drought in bulk soil, rhizosphere, and roots of wheat. We found that drought shifted microbial community structures, affecting fungi more strongly than prokaryotes. Microbial communities associated with crops (i.e. rhizosphere and root) were more strongly influenced by drought compared to bulk soil communities. A drought legacy effect was observed in the bulk soil after harvesting and rewetting. The resistance and resilience of the soil microbiome to severe drought did not significantly differ across the organic and conventional cropping systems, although few individual genera (e.g. Streptomyces, Rhizophagus, Actinomadura, and Aneurinibacillus) showed system-specific drought responses. All cropping systems showed relative increases in potential plant growth-promoting genera under drought. This agricultural field study indicated that fungal communities might be less resistant to drought than prokaryotic communities in cropping systems and these effects get more pronounced in closer association with plants. Organic fertilization or the reduction in pesticide application might not have the ability to buffer severe drought stress and additional farming practices might have to be incorporated to improve drought tolerance in cropping systems.